1, 2-Dibenzoylhydrazine - Sundara Raj, S. Shanmuga; Yamin, Bohari M.; Boshaala, Ahmed M. A.; Tarafder, M.T.H.; Crouse, Karen A.; Fun, Hoong-Kun (International Union of Crystallography, 2000)
In the crystal structure of the title compound, C14H12N2O2, the molecule lies about a twofold axis; two carbonyl groups and the H atoms of the N-N bond are in a trans orientation with respect to each other. In the crystal, each molecule is linked to the other and vice versa by intermolecular N-H⋯O hydrogen bonds between the amide hydrogen and the O atoms of neighbouring molecules to form two ten-membered rings, each of which has the graph-set motif C4R22(10). This extends as a polymeric chain along the c axis.